Analysis Of Charge Flow In Exhaust Manifold Of Acar - Sidup, Saiful Bahri (Universiti Sains Malaysia, 2004)
Many do not know and disregard the function of the exhaust system. In their mind, the exhaust system is just a system to dispose the exhaust gases; the result of the combustion process, out of the engine. In fact, the exhaust system also plays an important part in improving the engine’s performance. This analysis is dedicated to analyze the flow characteristics inside the exhaust manifold. The analysis is started by modeling the geometry of the exhaust manifold using I-DEAS. Then, the model is meshed using GAMBIT. Fina lly, the analysis is carried out using FLUENT after determining the boundary conditions, materials and other parameters needed for simulation. The results of this analysis are the velocity, temperature and pressure profile inside the exhaust manifold. Through this research, some ways of improving the design of the exhaust manifold has been found.